2003
DOI: 10.1590/s0100-879x2003000300006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in a Brazilian population with sickle-cell anemia

Abstract: Patients with sickle-cell anemia submitted to frequent blood transfusions are at risk of contamination with hepatitis C virus (HCV). Determination of HCV RNA and genotype characterization are parameters that are relevant for the treatment of the viral infection. The objective of the present study was to determine the frequency of HCV infection and the positivity for HCV RNA and to identify the HCV genotype in patients with sickle-cell anemia with a history of blood transfusion who had been treated at the Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
4
12
2
4
Order By: Relevance
“…This rate is higher than that of the blood donors in the region. Furthermore, the anti-HCV prevalence in the current study (12.5%) was lower than that ofthe multi-transfused patients in some neighbouring Arabic countries (29.4 to 44%) (23)(24)(25) and other countries such as Pakistan (48.6%) (26) and Brazil (14.1%) (13).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This rate is higher than that of the blood donors in the region. Furthermore, the anti-HCV prevalence in the current study (12.5%) was lower than that ofthe multi-transfused patients in some neighbouring Arabic countries (29.4 to 44%) (23)(24)(25) and other countries such as Pakistan (48.6%) (26) and Brazil (14.1%) (13).…”
Section: Discussioncontrasting
confidence: 64%
“…Recent studies of SCA patients show that the prevalence of anti-HCV varied (4.5 to 21%) (2,(11)(12)(13), which suggests that the geographical area may affect the potential risk of HCV in patients (17)(18)(19). Moreover, one of the most common causes of HCV transmission by transfusion is the occurrence of new infections in blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…These patients present the risk of acquiring the infection by hepatitis C virus from the blood transfusions to which they are submitted, 1,29 especially those who received blood transfusions before serum screening for anti-HCV antibodies in blood banks was started. A study performed in Pernambuco also showed an increased prevalence of infection by HCV among those individuals who had received more than 10 units of blood-based products.…”
Section: Gastrointestinal Systemmentioning
confidence: 99%
“…A study performed in Pernambuco also showed an increased prevalence of infection by HCV among those individuals who had received more than 10 units of blood-based products. 29 The prevalence of hepatitis C virus infection varies from 2 to 30% in individuals with sickle-cell anemia, when in the overall population it is estimated at 3%. 29 …”
Section: Gastrointestinal Systemmentioning
confidence: 99%
See 1 more Smart Citation